Could β-Lactam Antibiotics Block Humoral Immunity? - Melenotte, Cléa; Pontarotti, Pierre; Pinault, Lucile; Mège, Jean-Louis; Devaux, Christian; Raoult, Didier (Frontiers in Immunology, 2021)
It has been reported that treatment with β-lactam antibiotics induces leukopenia and candidemia, worsens the clinical response to anticancer immunotherapy and decreases immune response to vaccination. β-lactamases can cleave β-lactam antibiotics by blocking their activity. Two distincts superfamilies of β-lactamases are described, the serine β-lactamases and the zinc ion dependent metallo-β-lactamases. In human, 18 metallo-β-lactamases encoding genes (hMBLs) have been identified. While the physiological role of most of them remains unknown, it is well established that the SNM1A, B and C proteins are involved in DNA repair. The SNM1C/Artemis protein is precisely associated in the V(D)J segments rearrangement, that leads to immunoglobulin (Ig) and T-cell receptor variable regions, which have a crucial role in the immune response. Thus in humans, SNM1C/Artemis mutation is associated with severe combined immunodeficiency characterized by hypogammaglobulinemia deficient cellular immunity and opportunistic infections. While catalytic site of hMBLs and especially that of the SNM1 family is highly conserved, in vitro studies showed that some β-lactam antibiotics, and precisely third generation of cephalosporin and ampicillin, inhibit the metallo-β-lactamase proteins SNM1A & B and the SNM1C/Artemis protein complex. By analogy, the question arises as to whether β-lactam antibiotics can block the SNM1C/Artemis protein in humans inducing transient immunodeficiency. We reviewed here the literature data supporting this hypothesis based on in silico, in vitro and in vivo evidences. Understanding the impact of β-lactam antibiotics on the immune cell will offer new therapeutic clues and new clinical approaches in oncology, immunology, and infectious diseases.